1998
DOI: 10.1017/s0022112098001037
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent coagulation of colloidal particles

Abstract: Theoretical predictions for the coagulation rate induced by turbulent shear have often been based on the hypothesis that the turbulent velocity gradient is persistent (Saffman & Turner 1956) and that hydrodynamic and interparticle interactions (van der Waals attraction and electrostatic double-layer repulsion) between colloidal particles can be neglected. In the present work we consider the effects of interparticle forces on the turbulent coagulation rate, and we explore the response of the coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 10 publications
3
73
0
Order By: Relevance
“…in Wang et al, 2000;Zhou et al, 2001;Bec et al, 2005;Franklin et al, 2005;Bec et al, 2010). In a turbulent flow, however, the strain will not stay constant along the trajectory of a particle (Brunk et al, 1998) and it may be elliptic in some regions (Chong et al, 1990). Thus two particles can get close to each other, separate and come close again.…”
Section: Thementioning
confidence: 99%
“…in Wang et al, 2000;Zhou et al, 2001;Bec et al, 2005;Franklin et al, 2005;Bec et al, 2010). In a turbulent flow, however, the strain will not stay constant along the trajectory of a particle (Brunk et al, 1998) and it may be elliptic in some regions (Chong et al, 1990). Thus two particles can get close to each other, separate and come close again.…”
Section: Thementioning
confidence: 99%
“…Greene et al [39] extended the results of Zeichner and Schowalter to different extensional flow fields, containing different amount of vorticity, and demonstrated that the aggregation efficiency is almost unaffected by the flow type, except for flow types similar to the simple shear. More recently Brunk et al [40] [41] modeled the particle aggregation in turbulent conditions and systematically investigated the role of rotation on the coagulation rate. They confirmed the results of Zeichner and Schowalter and showed that stability ratio (W) is proportional to 23 .…”
Section: Orthokinetic Collision Efficiencymentioning
confidence: 99%
“…They developed a perturbation analysis of the pair probability equation for the relative motion of two particles with regard to diffusion and convection terms and came to the results that a little Brownian motion can either enhance or reduce the rate of rapid shear induced aggregation, depending on the flow number N f . Furthermore Brunk et al [40] pointed out that decreasing the shear rate while keeping N f constant, the aggregation efficiency for dilute suspensions with attractive interactions increases, since approaching particles will have many close encounters due to the Brownian motion, before they either collide or the flow carries them away from each other. On the other hand, at large total strain colliding particles have basically one opportunity for successful collision before the flow separates them.…”
Section: Orthokinetic Collision Efficiencymentioning
confidence: 99%
“…Notably, even in dilute systems, such turbulence-polymer couplings would most probably be entwined with both chain entanglement and hydrodynamic-interactions effects between chains in locally polymer-dense areas, as is the case, for example, in between turbulent coherent vortices where polymers might be expected to concentrate [14,24]. Similar ideas are also valid for turbulent flows in colloidal dispersions and aerosols [25], that feature particle aggregation/clustering phenomena [26,27] which require the capturing of hydrodynamic interactions between particles at high concentration areas, as is the case, for example, during rain initiation processes [28][29][30].…”
Section: Prologuementioning
confidence: 99%
“…Notably, even in dilute systems, such turbulence-polymer couplings would most probably be entwined with both chain entanglement and hydrodynamic-interactions effects between chains in locally polymer-dense areas, as is the case, for example, in between turbulent coherent vortices where polymers might be expected to concentrate [14,24]. Similar ideas are also valid for turbulent flows in colloidal dispersions and aerosols [25], that feature particle aggregation/clustering phenomena [26,27] which require the capturing of hydrodynamic interactions between particles at high concentration areas, as is the case, for example, during rain initiation processes [28][29][30].Therefore, there is a need for mesoscopic, physical formulations/numerical methods that allow the direct computation of turbulent polymeric (and colloidal) fluids. Such methods have to overcome a number of challenges: (a) the forcing of the fluid by the particles is delta-function type (i.e., pointwise), hence standard methods for computational fluid dynamics need an extremely fine grid in order to capture the microscopic flow field in between the particles that corresponds to their hydrodynamic interactions, (b) efforts to average the forced Navier-Stokes equations in order to overcome this problem, lead, due to nonlinearity, to the appearance of subgrid scale stresses that need to be taken into account via some type of modeling, (c) the accompanying numerical method needs to handle the Brownian, i.e., stochastic motion of polymer and colloidal particles; this adds an additional level of complexity to standard computational methods for suspensions [31], (d) in polymeric liquids, the formulation and numerics need to describe the formation and dynamics of entanglements between macromolecular chains, in order for the approach to be applicable to arbitrary polymer volume fractions.…”
mentioning
confidence: 99%